Internal Locus of Control dengan Kematangan Karier pada Mahasiswa Tingkat Akhir di Universitas Mulawarman - Hartia Adinda Tamara Putri; Aulia Suhesty (IDEA: Jurnal Psikologi, 2025)
Final-year students often have difficulty achieving career maturity due to a lack of mature career planning which also affects career decision-making. Many final-year students have not planned their careers properly. This study aims to determine the relationship between internal locus of control and career maturity in final-year students at Mulawarman University. The research method used is quantitative with a correlational approach. The sample used was 120 final-year students. The data collection method in this study used a Likert-type scale consisting of two scales, namely the career maturity scale and the internal locus of control scale. Validity and reliability tests were carried out on both scales. The analysis technique used was the Pearson Product Moment correlation and previously descriptive testing and assumption tests were carried out in the form of normality tests and linearity tests. The study results showed a strong and significant relationship between career maturity and internal locus of control in final-year students at Mulawarman University.